Early Modern Witches : Witchcraft Cases in Contemporary Writing. - Gibson, Marion (Taylor & Francis Ltd., 2000)
A collection of fifteen English witchcraft cases, some of which have never appeared in print before. It combines the original spelling editions of popular texts with scholarly annotation and will prove an essential resource to withcraft scholars.